1985
DOI: 10.1037/0022-3514.49.6.1513
|View full text |Cite
|
Sign up to set email alerts
|

Emotional reactions to a political leader's expressive displays.

Abstract: Forty college students viewed videotaped excerpts of happiness/reassurance, anger/ threat, and fear/evasion expressive displays by President Reagan. Within each display condition one excerpt was presented in image-only and one in sound-plus-image format. Emotional reactions were assessed by facial electromyography (EMG) from the brow and cheek regions and by skin resistance and heart rate. Following each excerpt, subjects also reported verbally the intensity of eight emotions. Self-reported emotions were influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
159
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(167 citation statements)
references
References 42 publications
6
159
0
1
Order By: Relevance
“…Thus, while emotional contagion of moods can occur without conscious processing (Hatfield, Caccioppo, and Rapson, 1992), when stronger emotions are on display, the social appropriateness of those emotions may then become more important. Also, as discussed at the beginning of this paper, while contagion can certainly be a subconscious process (McHugo et al, 1985), it need not be, and it can be influenced by both internal and external cues (e.g., Laird & Bresler, 1990). Lanzetta and Englis (1989) found that if subjects were led to believe they were having a cooperative interaction with a person, then convergent contagion occurred, that is, smiles led to smiles and autonomic relaxation, and grimaces led to grimaces and autonomic activation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while emotional contagion of moods can occur without conscious processing (Hatfield, Caccioppo, and Rapson, 1992), when stronger emotions are on display, the social appropriateness of those emotions may then become more important. Also, as discussed at the beginning of this paper, while contagion can certainly be a subconscious process (McHugo et al, 1985), it need not be, and it can be influenced by both internal and external cues (e.g., Laird & Bresler, 1990). Lanzetta and Englis (1989) found that if subjects were led to believe they were having a cooperative interaction with a person, then convergent contagion occurred, that is, smiles led to smiles and autonomic relaxation, and grimaces led to grimaces and autonomic activation.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals are more likely to adopt the view of persons they like than of those they dislike. For example, the emotions reported after watching a speech by then President Reagan determined whether viewers of a speech shared his emotions (McHugo et al, 1985). More specifically, the feelings of participants with a positive attitude toward Reagan were more congruent to his emotional display than were the feelings of participants with a negative attitude toward him.…”
Section: Methodsmentioning
confidence: 99%
“…To further scrutinize whether such an automatic form of perspective taking mediated the vicarious response, we thus decided to vary a second determinant of perspective taking. In addition to other factors, the attitude toward the target person is a well-known determinant of perspective taking (Batson, 1995;McHugo, Lanzetta, Sullivan, Masters, & Englis, 1985;Zillmann & Cantor, 1977). Individuals are more likely to adopt the view of persons they like than of those they dislike.…”
Section: Methodsmentioning
confidence: 99%
“…Imitation has an important role in human acquisition and processing of speech. Imitative tendencies are observed in many cognitive domains of human behaviour, such as reproducing actions and intentions of others (Hauser, 1996;Honorof et al, 2011;McHugo et al, 1985;Nagell et al, 1993). Such convergence may be evoked in imitation of single words (Goldinger, 1997(Goldinger, , 1998Goldinger & Azuma, 2004;Namy et al, 2002) as well in conversational interactions (Pardo, 2006;Pardo et al, 2010Pardo et al, , 2012).…”
Section: Imitationmentioning
confidence: 99%